IMPLEMENTASI METODE TALAQQI DALAM PEMBELAJARAN TAHSIN ALQUR’AN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA SISWA MADRASAH IBTIDAIYAH - Krisna Dian Sunanti (Jurnal Genta Mulia, 2026)
This study addresses the persistent problem of elementary-level students’ inadequate Qur’anic readingskills, particularly in fluency, makhārij al-ḥurūf, and tajwīd accuracy. It aims to describe and analyzethe implementation of the Talaqqi method in tahsin learning and to explain its role in improving theQur’anic reading ability of students at MI Sunanul Husna. The study employed a qualitativedescriptive approach involving one tahsin teacher and 22 students. Data were collected throughclassroom observation, in-depth interviews, and documentation, and were analyzed using the Miles andHuberman model, namely data reduction, data display, and conclusion drawing. The findings revealthat the Talaqqi method was implemented systematically through grouping students based on readingability, teacher modeling, attentive listening, repeated recitation, individual submission, and immediatecorrection. The method contributed to noticeable improvement in students’ reading fluency,pronunciation accuracy, and application of tajwīd rules. Its effectiveness was supported by teachercompetence, routine practice, student grouping, and parental involvement, although differences instudent ability and concentration remained challenges. The study concludes that Talaqqi is an effective and contextually relevant method for strengthening Qur’anic literacy in Islamic elementary educationand has practical implications for developing more personal, structured, and sustainable tahsininstruction.